Shelter Hewan Natha Nusantara di Jakarta Timur - Citra, Arizka Yulia; Schiffer, Lia Rosmala (Fakultas Teknik - Universitas Bung Karno, 2023)
Indonesia is one of the countries that downloads the most animal violence content and has more than 100 cases per year. In 2015, the animal welfare organization Natha Satwa Nusantara recorded 103 cases of violence against animals and this will continue to increase every year. Natha Satwa Nusantara as an animal welfare organization has built a shelter for abandoned animals and animals that need help. The shelter was built in Parung, Bogor with a capacity of 100 dogs and 200 cats, however, various problems have occurred in the surrounding environment. The 5 welfare principles put forward by the AVMA have been agreed upon and approved by all animal welfare organizations in the world. The point of freedom from fear and suffering has become a public issue that is highly highlighted by the eyes of the world. An animal shelter is a place or container or protection for abandoned animals. By providing protection for animals, it is hoped that this shelter can minimize fear and suffering. According to analysis and research, a suitable architectural concept is the concept of tropical industrial architecture.